Facilitator bureaucracy in Argentina - Calvert, Peter (1999)
Looking at public administration in Argentina under both military and civilian governments, the author focuses on role of bureaucracy in handling national economy from the crisis situation of hyperinflation to economic transformation under the new economic regime. Positioning itself in the First World even in the midst of most difficult circumstances, political and economic, the author shows success of bureaucracy in managing national economy while maintaining continuity and restoration of democracy with equipoise, and establishing newer State-society relationships. - Reproduced
Keywords: Bureaucracy - Argentina; Bureaucracy